Cuba in transition: Waking or awakening the socialist economy? - Fleming, Tom (America Magazine: The Jesuit Review of Faith & Culture, 1993)
Discusses Cuba's economic strategies during the transition from subsidized economy to self-sufficiency. Economic crisis spawned by absolute dependence on the Soviet Union with respect to export and import trades; Reduction of imports and increase in agricultural productivity; Introduction of market mechanisms and increase in privatizations; Developing the tourist industry.